Efficacy of Platelet-Rich Plasma Containing Xenogenic Adipose Tissue-Derived Stromal Cells on Restoring Intervertebral Disc Degeneration: A Preclinical Study in a Rabbit Model. (16th April 2019) - Ma, Chao; Wang, Ran; Zhao, Dingliang; Wang, Naikun; Han, Ying; Wang, Shichong; Gao, Tianyun; Wang, Bin; Lu, Lijuan
Abstract : Objective . Platelet-rich plasma (PRP) containing multiple growth factors is a promising strategy for disc degeneration. Thus, this study hypothesizes that the combination of PRP and adipose tissue-derived stromal cells (ADSCs) may repair degenerative disc more effectively than using each one of them alone. Methods . The model of early intervertebral disc degeneration was induced by annular puncture in the New Zealand rabbit. Autologous PRP was extracted from fresh arterial blood by using two centrifugation techniques. ADSC was offered by the Center for Clinic Stem Cell Research. Four weeks after the first experiment, PRP or ADSCs or a combination of PRP and ADSCs was injected into the punctured intervertebral disc. Four weeks later, disc height and signal intensity on T2-weighted magnetic resonance imaging (MRI) were assessed. Results . One month after puncture, we detected relatively narrow discs and lower signal intensity in MRI T2-weighted images. At four weeks after injection, the PRP-ADSC group statistically significantly restored discs, compared with PRP, ADSCs, or negative control group. Conclusions . The combination of PRP and ADSCs shows an effective potential to restore degenerated intervertebral discs in the rabbit.